Development of Tourism in Uzbekistan - Tadjiyeva Fayoza (Genius Journals, 2022)
This article talks about the development of tourism in Uzbekistan. Based on historical data, the author studied and analyzed specific aspects of the development of tourism in Uzbekistan based on available scientific literature.
Keywords: Uzbekistan; tourism; tourists; development